Perancangan dan Analisis Optimasi Metode Akuisisi Disk Paralel Menggunakan Python Thread dan Multiprocess Pada Odroid H4 Plus - Nugroho, Catur Adi; Sabila, Fadlilah Izzatus; Fauziah, Fauziah; Sholohati, Ira Diana (DPPM Universitas Pelita Bangsa, 2025)
Digital data acquisition in a forensic context requires high efficiency, especially when handling large-capacity storage media with limited power consumption devices such as Single Board Computers (SBCs). This study aims to design and evaluate a parallel disk acquisition tool based on the Odroid H4 Plus SBC with a multiprocess and thread approach. Three methods are compared: Serial DC3DD, Parallel DC3DD, and the Designed Method (parallel multiprocess and thread). Evaluations are conducted on various disk sizes (4GB, 16GB, 240GB, and 500GB) and two media types (USB and SATA), with key metrics including execution time, throughput, memory (RAM) usage, and hash validity. The test results show that the design method has the most efficient execution time, with significant time savings especially on large disks. The highest throughput is also achieved by this method, especially on SATA media. In terms of memory consumption, this method shows an increase in RAM usage of up to 32 MB, which is still within the light and efficient limits for SBC devices. All methods produce hash values identical to the reference hash, proving that data integrity is maintained. These findings demonstrate that a multiprocess and thread-based parallel approach effectively improves digital forensic acquisition performance significantly without sacrificing accuracy or resource efficiency. Future research can focus on optimizing buffer management, supporting a higher number of disks simultaneously, and integrating automation into a web-based interface to improve portability and ease of use